Irreversibilities and the timing of environmental policy - Robert S. Pindyck (Fondazione Eni Enrico Mattei (FEEM), 2000)
The standard framework in which economists evaluate environmental policies is cost-benefit analysis, so policy debates usually focus on the expected flows of costs and benefits, or on the choice of discount rate. But this can be misleading when there is uncertainty over future outcomes, when there are irreversibilities, and when policy adoption can be delayed. This paper shows how two kinds of uncertainty over the future costs and benefits of reduced environmental degradation, and over the evolution of an ecosystem interact with two kinds of irreversibilities - sunk costs associated with an environmental regulation, and "sunk benefits" of avoided environmental degradation - to affect optimal policy timing and design.
Keywords: Q28; L51; H23; 330; Environmental policy; irreversibilities; cost-benefit analysis; uncertainty; option value; global warming; Umweltpolitik; Kosten-Nutzen-Analyse; Risiko; Theorie